Diversity by Design - Johns, J (Apollo Magazine Ltd., 2016)
Review article discussing the exhibition "Sicily: Culture and Conquest", British Museum, London, 21 April – 14 August, 2016. The art of Norman Sicily is celebrated for its juxtaposition of Islamic, Byzantine and Romanesque elements - a remarkable feat of cultural engineering that was a deliberate display of power by the island's rulers.